LA IMPERSONALIDAD ACEPTADA DEL DISCURSO EN FACEBOOK: EL ESTATUS MÁS COMÚN ENTRE LOS JÓVENES - Manuel AYALA PALOMINO (Fonseca, Journal of Communication, 2023)
The social network Facebook has become a communication tool for millions of users worldwide, the present study was realized in order to know the characteristics of the discourse of the statuses, that element of this platform is used to present the users’ way of thinking at a given moment and this dictates how the other users will perceive each other, that this, along with the profile picture, those are the two main presentation elements. We analyzed the status discourse of 281 user profiles with an average age of 20 years.